Strategi Flipped Classroom dalam Meningkatkan Kreativitas Belajar Mahasiswa pada Materi Hadits Tarbawi di Era Digitalisasi - Aisyah Amalia Putri; Mohamad Agung Rokhimawan; H. Ahmad Fatoni; Teguh Gunawan; Risa Nalwi Fatimah (ISLAMIKA, 2023)
Low learning achievement, weak problem-solving skills and lack of motivation to compete in terms of goodness are problems of student learning creativity. The current era of digitalization is providing progress in the world of education. In tarbawi hadith material, students are expected to have competence in the form of being complete and expert in demonstrating the hadith of the prophet on educational theories and issues. The flipped classroom strategy is here to provide a solution to the above phenomenon. The aim of this study is to find out, describe, and analyze the flipped classroom strategy in increasing student learning creativity on tarbawi hadith material in the digitalization era. This study uses qualitative research with a descriptive approach. The data sources include students and lecturers. Data collection techniques using observation, interviews, and documentation. Data analysis techniques are in the form of critical analysis methods through several stages including; data reduction, data presentation, and drawing conclusions. The research results reveal that; 1) the flipped classroom strategy improves students' ability to think critically, confidently ask questions with weight, and be innovative in providing answers in learning discussions, classroom step which has reverse learning makes it easier for students to prepare for learning before entering a learning forum that is tailored to student's interests and learning styles, 3) the flipped classroom learning strategy through tarbawi hadith material is able to give enthusiasm to students and the spirit of doing good deeds in the digitalization era.